2017
DOI: 10.1080/13558358.2017.1351124
|View full text |Cite
|
Sign up to set email alerts
|

Conscientious objectors and the marrying kind: rights and rites in Dutch public discourse on marriage registrars with conscientious objections against conducting same-sex weddings

Abstract: When civil marriage in the Netherlands was opened up to same-sex couples in 2001, the Dutch government allowed civil marriage registrars with conscientious objections to opt out. This exemption became controversial in 2007, when it was reemphasized by a new government coalition that comprised two faith-based parties. Through critical discourse analysis this article discusses the construction of religion and homosexuality in public discourses on the weigerambtenaar (lit. 'refusing civil servant') between 2007 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Additionally, she wore a black gown as her ritual clothing which the couples expressed appreciation for while showing me pictures of it. In Finland, all marriage registrars are municipal employees and usually couples cannot choose a preferred marriage registrar (compare to Derks 2017). In other narrated rituals, the marriage registrars did not have a central role and these ceremonies had been conducted in a separate civil ritual.…”
Section: Couple Pastors and Guests As Actorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, she wore a black gown as her ritual clothing which the couples expressed appreciation for while showing me pictures of it. In Finland, all marriage registrars are municipal employees and usually couples cannot choose a preferred marriage registrar (compare to Derks 2017). In other narrated rituals, the marriage registrars did not have a central role and these ceremonies had been conducted in a separate civil ritual.…”
Section: Couple Pastors and Guests As Actorsmentioning
confidence: 99%
“…There are various recent studies on the relationship of state and church on same-sex rituals (Bos 2017; Derks 2017) but as a result of the Dutch context of these studies, they do little to shed light on the Nordic situation in which same-sex marriages are a more recent phenomenon. The Nordic context of same-sex partnerships has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…In the aftermath of the introduction of same-sex marriage, however, there was a lingering debate on the position of marriage registrars who did not want to conduct same-sex marriages at the city hall. As Marco Derks (2016; Derks, 2017) has argued, though the number of objecting registrars was relatively low, and various reasons for objections could be imagined besides biblical, Christian or even religious ones, the refusal to conduct same-sex marriages would soon be framed as a ‘social issue’ exemplary for what was generally understood as the necessarily homophobic attitude of Calvinist Christians. Through this framing of the backward Calvinist spoilsport a tolerant, emancipatory secular ‘we’ emerged that suggested that same-sex marriage advocacy had historically been a central part of Dutch culture instead of being a recent phenomenon.…”
Section: Secularism Vis-á-vis Christianity Islam and Colonialismmentioning
confidence: 99%